Pelaksanaan Pemasangan Alat Kontrasepsi IUD dan Inplant Gratis di Klinik Nirmala Medan Tahun 2022 - Kamaliah Kamaliah; Fatwiany Fatwiany; Elvi Sepriani (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
The family planning program is an effort to increase public awareness and participation through maturation of marriage age, birth control, fostering family resilience, and improving family welfare in order to realize a small, happy and prosperous family. IUD (Intra Uterine Device) is a plastic contraceptive that has a shape like the letter "T" and is installed in the uterus to prevent pregnancy Implant is a hormonal contraceptive method that is effective, not permanent and can prevent pregnancy between three and five years. This contraceptive is in the form of an empty silastic (silicone rubber) capsule filled with hormones and the ends of the capsule are sealed with silastic adhesive. Contraceptives are important for improving the quality of life of women and their families. They not only prevent unwanted pregnancies, but also reduce the number of abortions. And contraceptive use can help manage family income by spacing pregnancies and paving the way for women to work. Contraceptives have also been shown to lower maternal and infant mortality rates by spacing births and determining the number of children to be born. The use of long-acting contraceptives such as IUDs, implants, vasectomies, and tubectomies should be more widely promoted. The use of long-term contraceptives is the main need to reduce the rate of population increase.